2004
DOI: 10.1177/096739110401200807
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characterisation of Natural Fibre Reinforced Thermoplastics (NFRTP) Processed by Extrusion, Compression and Rotational Moulding

Abstract: In this paper we describe a methodology for applying conventional morphological characterization techniques to some of the manufacturing processes of natural fibre reinforced thermoplastics (NFRTP). The composites studied consisted of a matrix of polypropylene or polyethylene, and of discrete jute, sisal and other natural fibres as the reinforcement. Different microscopic techniques have been used to characterize the processing stages and the structure-property relationships during the manufacture of NFRTPs us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…Although limited information is available on this process, some studies on rotational molding with natural fibers have been found. Torres and Diaz conducted experiments with natural fibers (jute, sisal, cabuya and coir) with high density polyethylene (HDPE) as the matrix [14]. Ward and Rodrigue used pine fibers with linear medium density polyethylene (LMDPE) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Although limited information is available on this process, some studies on rotational molding with natural fibers have been found. Torres and Diaz conducted experiments with natural fibers (jute, sisal, cabuya and coir) with high density polyethylene (HDPE) as the matrix [14]. Ward and Rodrigue used pine fibers with linear medium density polyethylene (LMDPE) [15].…”
Section: Introductionmentioning
confidence: 99%
“…For these materials, their main applications are in transportation, civil infrastructure, sporting goods, packaging, as well as different commercial and engineering applications 8 . One reason for the growing commercial production of polymer composites is the interest being given to natural fibres (lignocellulosic) because they are ecologically and toxicologically harmless, biodegradable, CO 2 neutral, low cost and lightweight 911 .…”
Section: Introductionmentioning
confidence: 99%
“…But the polar and hydrophilic natural fibres are incompatible with most polymers which are non-polar and hydrophobic. This incompatibility leads to poor interface quality and poor mechanical performances 1014 . But good interfacial adhesion (compatibility) between natural fibres and polymer matrices can be achieved by using physical or chemical surface treatments 1315 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pengembangan prostesis atas lutut dengan menggunakan bahan komposit dengan serat alam belum dilakukan. Jika dilihat dari potensi serat alam yang besar di Indonesia seperti serat rami, dan isu tentang penggunaan bahan-bahan alami yang dapat didaur ulang dan ramah lingkungan, maka pengembangan prostesis atas lutut dengan bahan komposit serat rami mempunyai peluang yang cukup besar untuk diteliti dan dikembangkan lebih lanjut [7].…”
Section: Pendahuluanunclassified